Effects of peer mediation on preschoolers' compliance and compliance precursors. Issue 3 (12th August 2013) - Beaulieu, Lauren; Hanley, Gregory P.; Roberson, Aleasha A.
<x xml:space="preserve">Abstract</x> We used a multiple baseline design across participants to evaluate the effects of teaching 4 typically developing preschoolers to attend to their names and to a group call (referred to as precursors) on their compliance with typical classroom instructions. We then measured the extent to which the effects on both precursors and compliance were maintained when the teaching procedures were removed. Levels of compliance eventually decreased for all children. A multiple baseline design across participants was then used to evaluate the effects of peer mediation on the maintenance of precursors and compliance. Peer mediation involved teaching the children to either remind one another to engage in a precursor or praise one another for engaging in a precursor. Compliance improved with all children as a function of teaching precursors, and these changes were maintained through the use of peer mediation.